Pengaruh Kompetensi Terhadap Kinerja Karyawan Pada Pt. Silver Silk Tour And Travel Pekanbaru - Aqsa, Muhammad Ali; Fitrasyah, Hagil (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
In an organization required a system that can support the performance of the organization. One of them is a good competence and according to their respective fields of work. With the existence of a good competence certainly can support the work activities of employees more effectively and efficiently. The problem of the need to obtain superior and professional human resources expected by many companies in Indonesia both public and private business entities to compete in the current era of globalization. Coupled with the existence of Asean Economic Community (MEA), will certainly be a challenge for an organization. Today the world is characterized by an increasingly rapid development in all areas of activity, as well as in service activities. In general, the purpose of this study is to determine the effect of competence on employee performance at PT. Silver Silk Tour and Travel. The number of samples in this study as many as 53 people. The result in this research is competence has no significant effect on employee performance. The test equipment used in this study using simple linear regression, t test, and to determine the magnitude of the influence of variables using the coefficient of determination. In test the validity of the overall statement items between competence variables and performance variables declared valid because the value obtained rhitung> rtabel (0.270). Results of simple linear regression obtained value Y = 21.748 + 0.160X. From the test results partially or t test obtained tcount (1.096) <ttabel (2.007) with sig 0.278> 0.05 means competence variable is not significant to the performance variable. And the value of coefficient of determination R2 equal to 0.023 or 2.3%, it means Influence or contribution given by competence variable to performance variable equal to 2.3% while the rest equal to 97.7% influenced by other factor not examined in this research.